Experimental studies on the performance evaluation of water-soluble polymers used as temporary plugging agents - Wu, Guangai; Chen, Zhengrong; Zhang, Anshun; Zhou, Jun; Hou, Yanan; Xie, Xin; Wu, Jianshu; Kong, Xiangwei; Li, Song (Frontiers in Physics, 2023)
The performance of the temporary plug is a key factor in determining the success of loss-circulation control and temporary plug diversion fracturing. Due to the complexity of geomechanics and working conditions, current commonly used temporary plug agents face problems such as low plug strength and efficiency, large filtration losses due to failure to form filter cakes, and slow degradation affecting the recovery of fracture conductivity. A novel idea for the development of a novel water-soluble polymer plug for fracking is proposed, namely, low- to middle-molecule weight + reinforced chain rigidity + supramolecular aggregation. Using sodium bisulfite and potassium sulfate as initiators, AA, AM, and AMPS as grafting monomers, and SM as hydrophobic functional monomers, the AM-AA-AMPS-SM copolymer was prepared by polymerization. The developed new temporary plugging agent was completely degraded at 70 ℃ for 5-8 hours by carrying out experimental evaluation tests, such as water absorption expansion rate, swelling kinetics, density, post-dissolution viscosity, strength of the temporary plugging agent and post-degradation conductivity. After degradation, the viscosity of the solution is 2.5 - 3.6 mPa·s with good fluidity and no gel remnants. The density of the temporary plug material is about 1.14 g / cm3. The absorption expansion rate was 25.8 g / g. The pressure is 60.1 MPa when the thickness of the granular temporary plug is 0.4 cm. Under experimental conditions, the fracture conductivity was found to be 69-123 D*cm at a closing pressure of 30 MPa after degradation of the temporary plug. The test results demonstrate that the new temporary plug agent, with its high plug strength, temperature-controlled degradation, reflux stability and effective self-support after degradation, can meet the requirements of drilling plug and temporary plug fracturing technologies.